RUbble Biodiversity Samplers: 3D‐printed coral models to standardize biodiversity censuses. Issue 11 (25th August 2020) - Wolfe, Kennedy; Mumby, Peter J.
Abstract: To ensure standardized, quantitative and repeatable methodologies, marine ecologists have engineered a range of artificial units to survey benthic communities with varying designs depending on target taxa, life history stage and habitat. In tropical ecosystems, autonomous units have typically lacked microhabitat complexity (e.g. planar tiles), short‐term efficacy (<1 year deployment) and/or a truly standardized design to sample cryptobenthic diversity. Coral rubble is characterized by high microhabitat complexity, which is unresolved in sampling efforts. Yet, rubble can support the greatest density and diversity of metazoan taxa. We engineered RUbble Biodiversity Samplers (RUBS) as a dismantlable lightweight 3D‐printed model to standardize cryptobenthic biodiversity sampling. We demonstrate the effectiveness of RUBS with preliminary results from short‐term (1–14 days) deployments in Palau, Western Micronesia. RUbble Biodiversity Samplers uphold the microhabitat complexity inherent in coral rubble (~50% interstitial space) and provide an effective and efficient methodology to sample cryptobenthic fauna, which could be applied in comparative studies. The RUBS concept provides a platform for the broader implementation of 3D‐printed models in marine ecology to overcome issues of standardization regardless of habitat type.